A Quality Assessment of Tourist Information: the Case of Nautical Tourism at Shiretoko Peninsula - Neuts, Bart; Romão, João; Nijkamp, Peter; Shikida, Asami (Almatourism - Journal of Tourism, Culture and Territorial Development, 2014)
The success of tourism promotion in a destination partially depends on the extent to which it successfully links varied products catering to a heterogeneous group of visitors in a multi-client system. In contemporary destination marketing, communication between the service providers at the destination and the (prospective) tourists has become increasingly important as a result of the rise in informal communication channels and social media. This paper focuses on the effect of using different information sources when booking a cruise tour in Shiretoko Peninsula (a natural World Heritage Site) by employing a multi-group structural model. Our findings revealed that a mismatch between the expectation created by the visitors based on the information about the site and the satisfaction they experience when visiting the place can be a strong factor of dissatisfaction, with negative implications on the possible recommendations and loyalty. Additionally, it was possible to conclude that information available on the internet and via guidebooks seems to negatively affect satisfaction on certain elements and routes, while local information from tourist offices, hotels and local shops was found less problematic.